nn - Spaić, Bojan (Glasnik Advokatske komore Vojvodine, 2025)
The article discusses the relationship between philosophy of law and legal practice. It is argued that philosophy of law is a kind of thinking about law, which at the most general level can have the character of inspirational thinking and technical thinking. Both forms of legal philosophy can communicate with legal practice, but only technical legal philosophy can respond to specific legal problems. The article illustrates the approach by considering lawyerly reasoning and artificial intelligence. The article concludes by considering the importance of the philosophy of law for legal practice.
Keywords: philosophy of law, legal practice, technical thinking, inspirational thinking, legal reasoning, artificial intelligence.